Design and Development of Motion Graphic Promotional Video Content to Elevate Brand Exposure and Customer Engagement on the Instagram Platform @senji_id - Samosir, Nus Dencoco; Hidayat, Ahmad (Economic: Journal Economic and Business, 2025)
This study aims to develop promotional video content using motion graphics to enhance brand exposure and customer engagement on the Instagram account @senji_id. Initial data indicated that both the reach rate and engagement rate of the account were relatively low, highlighting the need for more engaging and relevant content strategies. The research employed a Research and Development (R&D) method with a Waterfall Model approach, which includes stages such as needs analysis, design, implementation, testing, deployment, and evaluation. Content validation was carried out by media and marketing experts, with results indicating that the developed videos were deemed suitable for publication. After being uploaded, the content showed an average increase in reach rate of 5.31% and engagement rate of 7.9%, categorized as very high. These findings demonstrate that motion graphics are an effective format for promotional content to improve business social media performance, particularly in building brand exposure and customer engagement.